Klug-entscheiden-Empfehlungen in der Kardiologie - Werdan, Karl; Katus, Hugo (Der Internist, 2017)
This article describes controversially discussed Choosing wisely recommendations presented by the German Cardiac Society: anticoagulation therapy in patients with atrial fibrillation and “only” moderate stroke risk, on the one hand, and goal-directed low-density lipoprotein (LDL) cholesterol-lowering, on the other. Presuming an adequate regime, patients with atrial fibrillation and only moderate risk of stroke (CHA2DS2-VASc Score of 1 in men and of 2 in women) also benefit from anticoagulation therapy, even in elderly patients. In patients with coronary heart disease, the German Cardiac Society recommends reducing LDL-cholesterol serum levels with a statin to values lower than 70 mg/dl (1.8 mmol/l) or at least reducing the basal level by 50%. With this recommendation, the German Cardiac Society unequivocally prioritizes the “goal-oriented statin therapy” above the “statin strategy of fixed dose”. The reasons for this preference are discussed.
Gesehen am 26.11.2018